An Ironless Large Displacement Flat Piston Loudspeaker - REMY, Mathias; LEMARQUAND, Guy; GUYADER, Gael (Archives of Acoustics, 2009)
This paper presents a small wide-band loudspeaker. Particular efforts have been made to reduce the nonlinearities of the loudspeaker as much as possible. The motor structure is completely ironless, the elastomer suspensions are replaced by ferrofluid seals and a monobloc carbon foam piston substitutes the traditional conic membrane. The circular radiating surface, which is flat, has a diameter equal to only 2cm. Therefore, in order to obtain a sufficient sound pressure level at low frequencies, large displacements of the piston are necessary. After a detailed description of each part of the loudspeaker, theoretical results of the expected performances of this transducer are given.